Bacterial lipases: impacts on dairy product quality and biotechnological potential (Research, Society and Development, 2021)
Lipases are enzymes that catalyze the hydrolysis of triacylglycerols, releasing fatty acids that can be associated with the spoilage of many foods. On the other hand, lipases of microbial origin present desirable characteristics to be used in several biotechnological applications and are considered versatile biocatalysts, acting in a variety of chemical reactions. The objective of this work was to evaluate, through a literature review, the impact of bacterial lipases on the quality of dairy products and the biotechnological potential of these enzymes. Psychrotrophic bacteria isolated from refrigerated raw milk commonly secrete heat resistant lipases, a problem for the dairy industry, as they resist heat treatments used and remain in the finished dairy product. Fatty acids released during lipolysis contribute to the strong, rancid, soapy taste of dairy products, making them unacceptable to the consumer. However, when this activity is controlled, lipases act in the development of desirable sensory attributes. For example, in some cheeses that mature for a long time, lipolytic activity is essential for the development of characteristic flavors. In addition, lipases have great potential for biotechnological application, including in the degradation of polyurethanes, representing an advantage for the industry. Therefore, lipases can cause defects in dairy products, but they are also of great industrial interest when their activity is explored.